Predictability of the Arctic sea ice edge. Issue 4 (24th February 2016) - Goessling, H. F.; Tietsche, S.; Day, J. J.; Hawkins, E.; Jung, T.
Abstract: Skillful sea ice forecasts from days to years ahead are becoming increasingly important for the operation and planning of human activities in the Arctic. Here we analyze the potential predictability of the Arctic sea ice edge in six climate models. We introduce the integrated ice‐edge error (IIEE), a user‐relevant verification metric defined as the area where the forecast and the "truth" disagree on the ice concentration being above or below 15%. The IIEE lends itself to decomposition into an absolute extent error, corresponding to the common sea ice extent error, and a misplacement error. We find that the often‐neglected misplacement error makes up more than half of the climatological IIEE. In idealized forecast ensembles initialized on 1 July, the IIEE grows faster than the absolute extent error. This means that the Arctic sea ice edge is less predictable than sea ice extent, particularly in September, with implications for the potential skill of end‐user relevant forecasts. Key Points: A new sea ice verification metric is introduced that discerns between total extent and misplacement Variability of the Arctic ice edge is dominated by misplacement rather than total extent Misplacement errors grow faster than extent errors due to scale‐dependent predictability